Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/pts.2540
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of α‐tocopherol‐loaded MCM‐41 mesoporous silica with different pore sizes and antioxidant active packaging films

Abstract: Antioxidant active packaging films were prepared with low-density polyethylene (LDPE) being incorporated with α-tocopherol-loaded MCM-41 mesoporous silica. In order to study the influence of pore size and morphology of the mesoporous material on physical and release properties of films, the mesoporous materials were synthesized with various pore sizes and morphologies. MCM-41 mesoporous silica materials before and after being loaded with α-tocopherol were characterized, as well as the active films. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Several articles observed a reduction in the crystallinity of the films as the inclusion or increase in the concentration of tocopherol in the films occurred; however, Jiang et al. (2021) observed an increase in crystallinity, attributed to the interaction between the plasticized PLA-PHB and α-tocopherol interface, corroborating Sun et al. (2020) who justified the increase of this parameter to the surface area of mesoporous silica nanoparticles added with tocopherol.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Several articles observed a reduction in the crystallinity of the films as the inclusion or increase in the concentration of tocopherol in the films occurred; however, Jiang et al. (2021) observed an increase in crystallinity, attributed to the interaction between the plasticized PLA-PHB and α-tocopherol interface, corroborating Sun et al. (2020) who justified the increase of this parameter to the surface area of mesoporous silica nanoparticles added with tocopherol.…”
Section: Resultsmentioning
confidence: 69%
“…, 2020; Sun et al. , 2017a, b, 2020, 2021). Furthermore, it can be attributed to the adequate pore size of the mesoporous silica that controlled the release rate (Sun et al.…”
Section: Resultsmentioning
confidence: 99%
“…This result demonstrated that PLA/IC could release CA faster than PLA/CA and the release process was less affected by PLA matrix than that of PLA/CA, which was consistent with the actual measured release of CA. This result is mainly due to the reason that the solubilization of β‐CD 47 significantly accelerates the release of CA.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 As a result, different antioxidants have been impregnated in several polymer films to protect food. 44 Some studies show that green tea extract (GTE) and oregano essential oil (OEO) released from ethylene-vinyl alcohol copolymer (EVOH), 43,45 a citrus extract from polyethylene terephthalate (PET), 46 and α-tocopherol from low-density polyethylene (LDPE) 47 all have antioxidant properties for food or simulants. Under the condition, the demand for antioxidants is different from the storage (the antioxidant is needed to stay in polymer for longer time during the storage), and it is expected to migrate to the polymer surface and take oxidation inhibition for food quickly when it contacts food.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the addition of MCM‐41 loaded with α‐tocopherol reduced the TS of the films while increasing the amount of NPs containing antioxidants restarted the release of α‐tocopherol from the film. The authors also showed that pore size, the morphology of MSNs, and type of surface modification influence the physical properties and release of LDPE films when incorporated with MCM‐41 loaded with α‐tocopherol (Sun, Lu, Pan, Lu, et al., 2021; Sun, Lu, Pan, Wang, et al., 2021). They found that the release rates of the antioxidant in packaging films can be adjusted by changing MCM‐41 pore size and functional groups, and the release period can be prolonged by 64%.…”
Section: Porous Nanomaterials As Robust Agents In Active and Smart Pa...mentioning
confidence: 99%